A case of severe dengue in a 5-year-old boy in the city of Lima - Bonifacio Morales, Nilo (2024)
Dengue is a viral infection which is transmitted by the Aedes aegypti mosquito and has four serotypes (DENV-1 to DENV-4). The disease triggers a variety of clinical manifestations, ranging from mild forms without warning signs to severe lifethreatening forms. We present the case of a 5-year-old boy, from the province of Callao, whose first symptoms were fever, headache and general malaise. On the third day, the child had mild abdominal pain and little vomiting; subsequently, abdominal distension, jaundice and choluria. He was admitted to the pediatric intensive care unit being alert and with moderate dehydration, jaundice, edema, distended and tender abdomen, shifting dullness and liver 2 cm below the right costal margin. Complementary tests revealed liver failure, hepatosplenomegaly and pleural effusion in the bases. Using a reactive IgM ELISA, severe dengue was diagnosed, as well as a superinfection due to probable spontaneous bacterial peritonitis. He started treatment with antibiotics, furosemide, fresh frozen plasma, cryoprecipitate and metamizole. As the child did not get better, the diuretic was optimized, and human albumin was administered. Thereafter, he got better showing decreased ascites, edema, jaundice and pleural effusion; improvement of the liver and coagulation profile; and being afebrile. He unexpectedly presented respiratory distress due to congestive heart failure caused by dilated cardiomyopathy diagnosed by echocardiography; thus, he was treated with diuretics. The patient was discharged afebrile, without edema and with resolution of liver failure and coagulation disorder.